2017
DOI: 10.1016/j.msec.2016.12.076
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties and in vivo study of modified-hydroxyapatite/polyetheretherketone biocomposites

Abstract: Polyether ether ketone (PEEK) has received much attention for its excellent mechanical properties and biocompatibility. Here, the silane coupling agent KH560 [γ-(2,3-epoxypropoxy)propyltrimethoxysilane] is used for graft modification of bioactive HA (hydroxyapatite) particles and for preparing HA/PEEK composites via a hot-press molding method. The prepared HA/PEEK composites were tested for their mechanical properties with SEM (scanning electron microscopy), infrared spectroscopy, and thermo-analysis. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…The layer of fibrous tissues developed between bioinert implants and host bone tissue may be long-term unstable, which may eventually result in the loosening and failure of implants [ 16 ]. Many investigations have been carried to improve the bioactivity of PEEK for promoting bone formation and osteointegration, and these strategies include surface modification with either physical/chemical ways, and composites with bioactive fillers were applied [ 17 , 18 ]. However, these simple surface modification with physical/chemical methods might not be practical to produce implants because of the potential incompatibility with sterilization and cleaning procedures [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The layer of fibrous tissues developed between bioinert implants and host bone tissue may be long-term unstable, which may eventually result in the loosening and failure of implants [ 16 ]. Many investigations have been carried to improve the bioactivity of PEEK for promoting bone formation and osteointegration, and these strategies include surface modification with either physical/chemical ways, and composites with bioactive fillers were applied [ 17 , 18 ]. However, these simple surface modification with physical/chemical methods might not be practical to produce implants because of the potential incompatibility with sterilization and cleaning procedures [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Ma et al had implanted various PEEK and HA-PEEK composite implants (of varying proportions) in rabbit tibias. They found that the HA-PEEK composites had increased push-out forces and interfacial shear strength relative to those of pure PEEK implants; the optimal amount determined by this study was 5 wt.% of HA (relative to higher concentrations of HA) [43] .…”
Section: Peek Compositesmentioning
confidence: 66%
“…Figure shows the FTIR spectra of the insoluble part of PLA/mHA compared with mHA and neat PLA. From the FITR curve of mHA, the sharp band observed at ∼3,570 cm −1 is attributed to the OH stretching mode of the OH ‐ ions in the lattice sites of mHA; the broad band at 3,300 cm −1 is attributed to the inner‐adsorbed water; the absorptions at 2,925 and 2,855 cm −1 belong to the CH 2  from KH560, indicating that the KH560 was successfully grafted onto the HA surface ; and the peak at 1,040 cm −1 is the characteristic peak of the normalPnormalO43 group of HA. On the FTIR spectrum of the insoluble part of PLA/mHA, in contrast with the curve of mHA, there were vibration peaks for the CO bond at 1748 cm −1 and a bending peak for the CH 3 group at 1,385 cm −1 , which are characteristic absorption peaks of PLA .…”
Section: Resultsmentioning
confidence: 99%